Implementation Of Khidmat Attitude In Shaping Students' Morals At Pertubuhan Kebajikan Al-Muhibbin Melaka, Malaysia - Sitorus, Panca Abdini; Ismaraidha, Ismaraidha (Riwayat: Educational Journal of History and Humanities, 2025)
This paper examines the impact of technological advances in the 5.0 era on the younger generation, especially Generation Z, who tend to experience a decline in moral values and morals. The focus of this study is to describe how the implementation of khidmat attitude can shape mahmudah morals at Pertubuhan Kebajikan Al-Muhibbin, Melaka, Malaysia. The research method used is qualitative, with data collection techniques through observation, in-depth interviews, and documentation. The findings of this study show that the implementation of khidmat attitude in this madrasa involves various activities such as cleaning the environment, providing food, preparing a place to study, reading the Khulaso wirid, practicing the Ba'alawi tariqah, and pilgrimage to the graves of the founders of the foundation, ulama, and habaib. This study recommends further research to examine the application of khidmat, not only in madrasah but also at home, as an effort to strengthen moral and moral values among the younger generation.